A Bibliometric Analysis of 100 Most-Cited Articles on Corneal Cross-Linking - Yang, Kaili; Xu, Liyan; Wang, Shaopei; Zhu, Meng; Fan, Qi; Gu, Yuwei; Wang, Yawen; Wang, Qing; Zhao, Dongqing; Pang, Chenjiu; Ren, Shengwei (Frontiers in Medicine, 2022)
Background: Highly cited papers are expected to have high-quality data that significantly contribute to the body of knowledge. The study aimed to evaluate the characters of 100 most-cited articles on corneal cross-linking (CXL) through a bibliometric analysis. Methods: The Web of Science database was searched to identify papers published from 1950 to 2020. A bibliometric analysis of the top 100 cited articles was conducted in the current study. The citation differences between basic research, clinical research, and reviews were compared by Kruskal-Wallis test. The association between citations and publication year was evaluated by Spearman correlation analysis. The VOSviewer software was used to create networks of co-authorship and keywords map. Results: The median values of the number of citations, citations/year since publication, and citations since 2013 were 101, 9.5, and 11.92, respectively. A total of 61% of articles were clinical research. The citations since 2013 of clinical research were lower than basic research and the reviews (all P<0.001). The publication year was positively correlated with the number of publications (r=0.665, P=0.013), and the total number of citations decreased for basic research (r=-0.447, P=0.017) and clinical research (r=-0.433, P<0.001). J REFRACT SURG publishing the highest number of articles. The corresponding authors were predominantly from the Italy (N=17), Germany (N=16) and USA (N=15). Spoerl Eberhard has the highest number of citations and total link strength with 15 articles. Extensive collaboration existed among the main core nodes containing “cross-linking (N=45)”, “riboflavin (N=44)”, and “uva(N=42)”. Conclusions: The present study focused on the comprehensive analysis of the top 100 cited articles on corneal CXL research, providing insight into research developments over the past decades.